Perfil de internações e prevalência de condições sensíveis à atenção primária em hospital universitário - Lucia Aparecida de Souza; Ricardo de Mattos Russo Rafael; Anna Tereza Miranda Soares de Moura; Mercedes Neto (Universidade Federal do Ceará, 2017)
Objective: to describe the profile of hospitalizations and the prevalence of conditions sensitive to primary care in the medical clinic sector. Methods: exploratory cross-sectional study with 197 subjects hospitalized for over 24 hours. Data collected from interviews and medical records collection of hospitalized patients in the sector and analyzed through descriptive statistics. Results: adults, females, black skinned people, with 4-12 years of schooling, belonging to class C and residents of the urban zone predominated among the hospitalized people. The prevalence of hospitalizations due to sensitive conditions was 20.8% (Confidence Interval 95.0%: 15.7/27.1). Diseases of the respiratory tract, skin and subcutaneous tissue presented higher prevalence than the general estimate of hospitalizations for conditions sensitive to Primary Care. Conclusion: hospitalizations occurred predominantly in middle-class adults with up to 12 years of schooling. The frequency of hospitalizations due to sensitive conditions was high, and mainly due to circulatory, respiratory, digestive and genitourinary diseases.